Women on park benches with banner - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows a group of women sitting on two park benches. Behind them is a banner that reads, "Ann Arbor says closets are for clothes". The women are participating in the National March on Washington for Lesbian and Gay Rights.